Vegetable Storage Procedures in the Hotel Kitchen: A Case Study at Grand Seminyak Lifestyle Boutique Bali Resort - Degong, Emiliana Florentina; Sunata, I Made; Raditya, I Putu Tiana (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
This study examines vegetable storage procedures in the kitchen of Hotel Grand Seminyak Lifestyle Boutique Bali Resort. The hospitality industry demands strict adherence to food safety and storage standards to ensure guest health and operational efficiency. Observations revealed challenges including chiller instability, inconsistent FIFO application, and limited storage space. Using a descriptive qualitative method through observation, interviews with executive sous chef and commis, and documentation, the study identifies seven procedural stages: receiving, sorting, cleaning, placement, chiller storage at 4–8°C, FIFO application, and periodic inspection. Key constraints include storage space limitations, variable supplier quality, improper stacking, and equipment malfunctions. Mitigation efforts include systematic reorganization, stricter quality checks at receiving, consistent FIFO enforcement, and routine chiller temperature monitoring. The study concludes that while procedural frameworks are established, consistency gaps exist between standard operating procedures and actual kitchen practice, particularly during peak operational periods.